Reviewing Sex - Thompson, N. author. aut Link
XII, 164 p.
Keywords: Reviewing Sex: Gender and the Reception of Victorian Novels looks at the influence of Victorian definitions of gender on the cultural processes of reading and canon formation in nineteenth-century England, examining the reception of several mid-century works in over 100 Victorian book reviews. This study investigates four canonical and popular novelists (Emily Bronte, Anthony Trollope, Charles Reade, Charlotte Yonge), all of whom caused high cultural commotions by epitomizing or subverting contemporary definitions of 'masculine' or 'feminine' writing.